Management of dental extraction in a female patient with fanconi anemia. - Andre Peisker; Gregor Franziskus Raschke; Arndt Guentsch; Korosh Roshanghias; Stefan Schultze-Mosgau (Tehran University of Medical Sciences, 2014)
Oral surgery in patients with bleeding disorders is associated with a high risk of bleeding during and after surgery. This article is aimed to present the case of an eight-year-old girl suffering from severe Fanconi anemia with pancytopenia who underwent a dental extraction. The hemostatic effect of local administration of tranexamic acid in combination with a primary suture seems to be extremely helpful in order to reduce the necessity of blood products and the risk of postoperative bleeding.